CXL-1020, a Novel Nitroxyl (HNO) Prodrug, Is More Effective than Milrinone in Models of Diastolic Dysfunction—A Cardiovascular Therapeutic: An Efficacy and Safety Study in the Rat - Roof, Steve R.; Ueyama, Yukie; Mazhari, Reza; Hamlin, Robert L.; Hartman, J. Craig; Ziolo, Mark T.; Reardon, John E.; del Rio, Carlos L. (Frontiers in physiology, 2017)
The nitroxyl (HNO) prodrug, CXL-1020, induces vasorelaxation and improves cardiac function in canine models and patients with systolic heart failure (HF). HNO's unique mechanism of action may be applicable to a broader subset of cardiac patients. This study investigated the load-independent safety and efficacy of CXL-1020 in two rodent (rat) models of diastolic heart failure and explored potential drug interactions with common HF background therapies. left-ventricular hemodynamics/pressure-volume relationships assessed before/during a 30 min IV infusion of CXL-1020 demonstrated acute load-independent positive inotropic, lusitropic, and vasodilatory effects in normal rats. In rats with only diastolic dysfunction due to bilateral renal wrapping (RW) or pronounced diastolic and mild systolic dysfunction due to 4 weeks of chronic isoproterenol exposure (ISO), CXL-1020 attenuated the elevated LV filling pressures, improved the end diastolic pressure volume relationship, and accelerated relaxation. CXL-1020 facilitated Ca re-uptake and enhanced myocyte relaxation in isolated cardiomyocytes from ISO rats. Compared to milrinone, CXL-1020 more effectively improved Ca reuptake in ISO rats without concomitant chronotropy, and did not enhance Ca entry via L-type Ca channels nor increase myocardial arrhythmias/ectopic activity. Acute-therapy with CXL-1020 improved ventricular relaxation and Ca cycling, in the setting of chronic induced diastolic dysfunction. CXL-1020's lusitropic effects were greater than those seen with the cAMP-dependent agent milrinone, and unlike milrinone it did not produce chronotropy or increased ectopy. HNO is a promising new potential therapy for both systolic and diastolic heart failure.